Ethical Issues in the Management of Helicobacter pylori Infection - Anthony Axon (Canadian Journal of Gastroenterology)
Medical ethics are not absolute; they change according to social attitudes, technological advances and alterations in the doctor/patient relationship. The discovery of Helicobacter pylori highlighted entrenched attitudes in academia and the pharmaceutical industry that were not always appropriate. The explosion of research that followed was ethically controlled by local research ethics committees and the system of peer review and editorial responsibility. Now that effective treatments are available, the control arm in trials of new therapy should be either placebo (giving the option of effective treatment later) or a first-line treatment; mono and dual therapy should not be employed because of the risk of inducing bacterial resistance. Ethical issues that still remain include whether always to test patients for H pylori at endoscopy and what information should be given when they test positive. The most important issue is the approach of the medical profession to the high death rate carried by H pylori infection. Peptic ulcer and gastric cancer together account for a large number of deaths worldwide, and the medical profession and public health services have not yet grappled with this problem, neither advocating universal testing and treatment nor funding or research to determine whether this approach would be effective.